Best Answer

a+b = 17

a+c = 36 ----> c = 36 - a

b+c = 25 ----> c = 25 - b

So since both are c, we say

36 - a = 25 -b

From this : 11 = a - b

Look at 1st eqn: a + b = 17

Now we have: a - b = 11 ----> a = 11 + b

So we can substitute that into a + b = 17 to make:

(11 + b) + b = 17

11 + 2b = 17

So b = 3

If b = 3, then a + 3 = 17 , so a = 14

, 3 + c = 25, so c = 22

So a=14, b=3, c=22, so a+b+c = 14+3+22 = 39

Q: What is a plus b plus c if a plus b equals 17 a plus c equals 36 and b plus c equals 25?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

28 plus 17 plus 25 plus 54 plus 20 plus 36 is equal to 180.

132

72

36-h equals 61 = -25

36 has more factors than 6, 17 and 25.

Related questions

28 plus 17 plus 25 plus 54 plus 20 plus 36 is equal to 180.

36 + 4 - 8 -7 = 25

36

The answer is 636 36 + 17 = 53 636 / 53 = 12

36+4=40 40-8=32 32-25 equals=7 answer

5 plus 25 equals 60. Need to solve for 5 plus 25 equals ?: 2 plus 10 equals 24 is equivalent to 2 × (1 plus 5) equals 2 × (12); and 3 plus 15 equals 36 is equivalent to 3 ×(1 plus 5) equals 3 × (12); thus 5 plus 25 equals ? is equivalent to 5 × (1 plus 5) equals 5 × (12); thus ? = 5 × 12 = 60.

52 times 36 equals 1,872, plus 17 equals 1,889.

-36

-36

132

9 out of 36 equals 25%

62